Pharmacogenomics in Pediatric Cancer Patients Treated with Irinotecan: A Systematic Review - Nisarga P; Ramdas Bhat; Sinchana S Bhat (Oral Sphere Journal of Dental and Health Sciences, 2025)
Background: Irinotecan, a vital chemotherapeutic in pediatric oncology, often causes severe toxicities, including grade 3-4 neutropenia and diarrhoea. These adverse events are strongly linked to interpatient variability in the metabolism of its active metabolite, SN-38, primarily by the UDP-glucuronosyltransferase 1A1 (UGT1A1) enzyme. Polymorphisms like UGT1A1*28 and *6 impair this detoxification, increasing toxicity risk. While UGT1A1 genotyping is standard for adults, pediatric-specific guidelines are lacking due to developmental differences in enzyme expression and pharmacokinetics. This systematic review aims to synthesize evidence on UGT1A1 pharmacogenomics in pediatric cancer patients receiving irinotecan, focusing on genotype-toxicity associations, implementation challenges, and research gaps. Methodology: Following PRISMA guidelines, we searched PubMed, Scopus, and EMBASE (January 2000 – August 2025). Included studies involved pediatric patients (